S35 A randomised controlled trial comparing combined EBUS/EUS followed by surgical staging versus surgical staging alone in non-small cell lung cancer: the ASTER study. (16th November 2010) - Rintoul, R C; Tournoy, K G; Dooms, C; De Leyn, P; Nicholson, A G; Deschepper, E; Dekkers, O M; Rabe, K F; van Meerbeeck, J P; Annema, J T
Abstract : Background: For many years the standard approach to staging of the mediastinum in non-small cell lung cancer (NSCLC) has been surgical using cervical mediastinoscopy, left anterior mediastinotomy or video assisted thoracoscopic surgery (VATS). More recently endobronchial ultrasound (EBUS) and endoscopic ultrasound (EUS) have been reported. We conducted a randomised phase III trial to compare surgical staging versus endoscopic staging. The primary endpoint was detection of mediastinal nodal metastasis (N2/3); secondary endpoints were complication and futile thoracotomy rates. Methods: Consecutive patients with potentially resectable (suspected) NSCLC in whom invasive mediastinal staging was indicated based on CT or PET-CT findings were randomly assigned to either Arm A, surgical staging or Arm B, combined EBUS/EUS (followed by surgical staging if endoscopic findings were negative for malignancy). Surgical staging involved mediastinoscopy and/or mediastinotomy and/or VATS. Subsequently, in the absence of mediastinal disease, thoracotomy with systematic lymph node sampling was performed. 240 pts were required to show a 20% increase in sensitivity (power 80% and α=0.05) to detect mediastinal nodal disease with a prevalence of 50%. Results: 118 patients were randomised to Arm A and 123 to Arm B. The sensitivity for detection of mediastinal metastases by surgical staging in Arm A was 80% (95% CI, 68 to 89) vs 94% (95% CI, 85 to 98) for endoscopic (± surgical) staging in Arm B (p=0.04). Nodal metastases were found in 41 (35%) of surgically staged patients in Arm A and 62 patients (50%) (56 by EBUS/EUS + 6 by subsequent surgical staging) in Arm B (p=0.019). Overall, the prevalence of mediastinal disease in each arm was similar (p=0.24). Thoracotomy was considered futile in 21 (18%) in those staged in Arm A vs 8 patients (7%) in Arm B (p=0.009). Complication rate was similar in both arms (6 vs 7 patients, p=0.8); however, 12 of 13 complications were due to surgical staging procedures. Conclusions: Mediastinal staging for NSCLC should commence with combined EBUS/EUS (followed by surgical staging if endoscopic findings are negative for malignancy) as this improves the detection of nodal metastases and reduces futile thoracotomies compared to surgical staging alone.